Barriers to the secondary use of data in critical care. (May 2018) - Prince, Karl; Jones, Matthew; Blackwell, Alan; Simpson, Alexander; Meakins, Sallyanne; Vuylsteke, Alain
Purpose: We explore the challenges of the secondary use of data in clinical information systems which critical care units in the National Health Service (England) are facing. Methods: We conducted an online survey of critical care units in England regarding their practices in collecting and using clinical information systems and data. Results: Critical care units use clinical information systems typically independently of hospital information systems and focus mainly on using data for auditing, management reporting and research. Respondents reported that extracting data from their clinical information system was difficult and that they would use stored data more if it were easier to access. Data extraction takes time and who extracts data, the training they receive and the tools they use affect the extraction and use of data. Conclusion: A number of key challenges affect the secondary use of data in critical care: a lack of integration of information systems within critical care and across departments; barriers to accessing data; mismatched data tools and user requests. Data are predominantly used for reporting and research with less emphasis on using data to inform clinical practice.